SLC40A1-mediated positive feedback loop with M1 macrophages suppresses epithelial ovarian cancer progression - Wang, Guangyan; Huang, Sisi; Yin, Bo; Shangguan, Fugen; Ma, Jinghang; Li, Anyang; Xia, Zhexin; Xu, Zhenzhen; Li, Yuheng; Jin, Honglei; Hu, Yan; Huang, Baoyou (Frontiers in Immunology, 2026)
IntroductionOvarian cancer (OC), particularly epithelial ovarian cancer (EOC), represents one of the most lethal and aggressive gynecological malignancies. Despite advances in surgery, chemotherapy, and immunotherapy, patient survival remains poor. Identifying novel molecular targets is crucial for improving early diagnosis and developing more effective therapies.MethodsWe examined the expression and immunoregulatory function of SLC40A1 in EOC using both experiments on cells and mouse orthotopic tumor models. Through integrated in vitro and in vivo studies, we systematically assessed the role of SLC40A1 in promoting M1 macrophage polarization and its relationship with tumor suppression, demonstrating that SLC40A1 enhances the response to immunotherapy.ResultsSLC40A1 was found to be more highly expressed in normal ovarian tissues compared with EOC tissues, and its high expression was associated with a favorable prognosis. In vitro, SLC40A1 did not significantly affect tumor cell proliferation, apoptosis, or migration and invasion. However, in vivo experiments using mice with differing immune status demonstrated that SLC40A1 modulates the tumor immune microenvironment. Subsequent bioinformatics analyses suggested that SLC40A1 may regulate M1 macrophage polarization. Mechanistically, in vitro experiments confirmed that SLC40A1 regulates CXCL11 secretion, which activates the JAK2–STAT1 signaling pathway, promoting macrophage TNF-α production, which in turn upregulates SLC40A1 expression. Finally, we demonstrated that SLC40A1 enhances the response to immunotherapy.DiscussionThese findings identify SLC40A1 as a key regulator of the antitumor immune response in EOC. High SLC40A1 expression is associated with enhanced macrophage-mediated tumor suppression and improved response to immunotherapy, highlighting its potential as both a prognostic biomarker and a therapeutic target.